The effect of electronic chapters in the three pictures (interactive - cooperative - integrative) in the achievement of middle school students in the Arabic grammar - Salman Alqece, Huda Mohammed (Opción, 2019)
The research aims at the effect of the electronic chapters in the three images interactively cooperative integrative in the achievement of the students of the first medium with the rule of Arabic grammar. The sample of the research consisted of 78 students. The researcher put the null hypothesis. There are no statistically significant differences at the level of 05.0 between the post- Level (remember understanding application) Among the three groups (interactive e-chapter), e-mail, e-learning, e-learning, e-learning, e-learning, e-learning, and e-learning. The researcher made some suggestions - Promoting awareness of the importance of e-learning through training programs. The establish- ment of specialized training courses in the field of applications of e-learning and educational design through universities and specialized institutes orienta- tion towards consideration of the curriculum